Foreign Investments of U.S. Individual Investors: Causes and Consequences - Bailey, Warren; Kumar, Alok; Ng, David (Management Science, 2008)
Using thousands of brokerage accounts of U.S. individual investors, we analyze the motivations and consequences of foreign equity investment. We find that diversification is not the only reason that investors trade foreign securities. While wealthier, more experienced investors enjoy an informational advantage and, thus, are more likely to invest overseas and experience good portfolio performance, other investors appear to venture abroad for the wrong reasons. In particular, behaviorally biased investors often underuse or misuse foreign equity securities and experience poor portfolio performance. Some investors appear to use foreign securities for speculation or to improve upon poor domestic portfolio performance.